General vaccination coverage before and during the covid-19 pandemic in Brazil: A cross-sectional study - Manoel, Poliana Zanotto (2024)
OBJECTIVE: The objective of this study is to analyze the general vaccination coverage of all immunobiologicals offered by the National Immunization Program (PNI) before (2018-2019) and during the COVID-19 pandemic (2020-2021) in the Brazilian territory, by region and capital. METHODOLOGY: It was carried out a cross-sectional study, with secondary data from PNI via the Department of Informatics of the Unified Health System (DATASUS). Data were tabulated and submitted to statistical tests, including the Shapiro-Wilk test to verify normality and Pearson and Spearman correlation tests. RESULTS: 407,570,811 doses of immunobiologicals were applied in Brazil, the overall average vaccination coverage for the period (2018-2021) was 69.4%, showing a sharp downward trend, which ranged from 75.2% in the pre-pandemic period to 63.7% in the pandemic. CONCLUSION: During the pandemic there was a decrease in national vaccination compared to the period before it, especially in the North and Northeast regions. In this way, the pandemic may have contributed to the reduction of immunizations.